On-farm Participatory Assessment of Short and Medium Duration Rice Genotypes in South-western Punjab - Singh, Pritpal; Singh, Gurdeep; Sodhi, GP S (Indian Journal of Extension Education, 2020)
The study reports the performance of short and medium-duration rice genotypes (viz. PR-126, PR-122, and PR- 124) via front-line demonstrations (FLDs) on low-fertility soils irrigated with poor-quality underground water in south-western Punjab, India. A total of 550 FLDs were conducted during two consecutive years (kharif 2018 and 2019) at farmers' fields in different villages. The average rice grain yield of PR-122 was significantly higher by ~11.1 and 14.5 per cent, compared with PR-126 and PR-124, respectively. The mean net returns (MNRs) wereÂ significantly higher for PR-122 by Rs.12,778/- ha-1 and Rs. 16,818/- ha-1, compared with PR-126 and PR-124, respectively. PR-122 had significantly higher B:C, compared with the other two genotypes in the south-western Punjab. The yield gap assessed from average yield potential was higher for PR-124 and the lowest for PR-126, while for PR-122 in between. However, the production efficiency of 54.5 kg ha-1 day-1 was higher for PR-126, compared with PR-124 (50.0 kg ha-1 day-1) and PR-122 (50.6 kg ha-1 day-1). The economic efficiency of PR-124Â was lower by ~ Rs. 111.9 ha-1 day-1 and Rs. 43.6 ha-1 day-1 than PR-126 and PR-122, respectively. The waterÂ use efficiency was higher for PR-126, compared with the other two genotypes. The extension gap varied between -0.59 and -1.21 Mg ha-1 for three genotypes, with highest gap for PR-126 and the lowest for PR-124. The technology index varied between 5.6 and 14.8 per cent, and was the highest for PR-124 and the lowest for PR-122.